Repolarization of macrophages to improve sorafenib sensitivity for combination cancer therapy. (May 2023) - Huang, Linzhuo; Xu, Rui; Li, Weirong; Lv, Li; Lin, Chunhao; Yang, Xianzhu; Yao, Yandan; Saw, Phei Er; Xu, Xiaoding
Abstract: Sorafenib is the first line drug for hepatocellular carcinoma (HCC) therapy. However, HCC patients usually acquire resistance to sorafenib treatment within 6 months. Recent evidences have shown that anticancer drugs with antiangiogenesis effect ( e.g., sorafenib) can aggravate the hypoxia microenvironment and promote the infiltration of more tumor-associated macrophages (TAMs) into the tumor tissues. Therefore, repolarization of TAMs phenotype could be expected to not only eliminate the influence of TAMs on sorafenib lethality to HCC cells, but also provide an additional anticancer effect to achieve combination therapy. However, immune side effects remain a great challenge due to the non-specific macrophage repolarization in normal tissues. We herein employed a tumor microenvironment (TME) pH-responsive nanoplatform to concurrently transport sorafenib and modified resiquimod (R848-C16). This nanoparticle (NP) platform is made with a TME pH-responsive methoxyl-poly(ethylene glycol)- b -poly(lactic- co -glycolic acid) copolymer. After intravenous administration, the co-delivery NPs could highly accumulate in the tumor tissues and then respond to the TME pH to detach their surface PEG chains. With this PEG detachment to enhance uptake by TAMs and HCC cells, the co-delivery NPs could combinatorially inhibit HCC tumor growth via sorafenib-mediated lethality to HCC cells and R848-mediated repolarization of TAMs into tumoricidal M1-like macrophages. Statement of significance: Anticancer drugs with antiangiogenesis effect ( e.g ., sorafenib) can aggravate the hypoxia microenvironment and promote the infiltration of more tumor-associated macrophages (TAMs) into the tumor tissues to restrict the anticancer effect. In this work, we designed and developed a tumor microenvironment (TME) pH-responsive nanoplatform for systemic co-delivery of sorafenib and resiquimod in hepatocellular carcinoma (HCC) therapy. These co-delivery NPs show high tumor accumulation and could respond to the TME pH to enhance uptake by TAMs and HCC cells. With the sorafenib-mediated lethality to HCC cells and R848-mediated repolarization of TAMs, the co-delivery NPs show a combinational inhibition of HCC tumor growth in both xenograft and orthotopic tumor models. Graphical Abstract: Image, graphical abstract